2019
DOI: 10.1039/c8en01418c
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric detection of heavy metal ions using fluorescent carbon dots

Abstract: Classical methods for the detection of heavy metal ions in water are tedious and time consuming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 56 publications
4
72
0
Order By: Relevance
“…Purification of wastewater using novel environmentally friendly methods is becoming a hot research topic from the last few decades (Yu et al, 2017;Bolisetty et al, 2019). Several classical methods are reported in the literature for the selective detection of Hg 2+ and Pb 2+ , including atomic absorption spectrometry, ICP-MS method (Karunasagar et al, 1998;Fong et al, 2007), GC-atomic fluorescence (Nevado et al, 2005), HPLC (Kodamatani et al, 2012), Fluorescence sensor (Chang et al, 2007;Chiang et al, 2008), conjugated polymers (Liu et al, 2007), ratiometric (Yarur et al, 2019), oligonucleotides (Ono and Togashi, 2004;Lin et al, 2011;Lu et al, 2013), proteins (Guo and Irudayaraj, 2011), bioluminescent bacterial sensors (Durand et al, 2015), and electrochemical sensing (Zhu et al, 2017) etc. All the above-mentioned methods used expensive instrumentation, time-consuming sample preparation steps, and more laborious.…”
Section: Introductionmentioning
confidence: 99%
“…Purification of wastewater using novel environmentally friendly methods is becoming a hot research topic from the last few decades (Yu et al, 2017;Bolisetty et al, 2019). Several classical methods are reported in the literature for the selective detection of Hg 2+ and Pb 2+ , including atomic absorption spectrometry, ICP-MS method (Karunasagar et al, 1998;Fong et al, 2007), GC-atomic fluorescence (Nevado et al, 2005), HPLC (Kodamatani et al, 2012), Fluorescence sensor (Chang et al, 2007;Chiang et al, 2008), conjugated polymers (Liu et al, 2007), ratiometric (Yarur et al, 2019), oligonucleotides (Ono and Togashi, 2004;Lin et al, 2011;Lu et al, 2013), proteins (Guo and Irudayaraj, 2011), bioluminescent bacterial sensors (Durand et al, 2015), and electrochemical sensing (Zhu et al, 2017) etc. All the above-mentioned methods used expensive instrumentation, time-consuming sample preparation steps, and more laborious.…”
Section: Introductionmentioning
confidence: 99%
“…17 As a result, various types of uorescent probes such as organic dyes, magnetic nanoparticles (MNPs), semiconductor quantum dots (QDs), carbon dots (CDs), uorescent metal nanoclusters (NCs), and uorescent metal organic frameworks (MOFs) have been designed and prepared to determine Cu 2+ ion. [18][19][20][21][22][23][24][25][26][27] Since rst reported in 2000, MNPs are extensively used in the eld of nanotechnology for its nonhazardous feature, strong magnetization values, superparamagnetic property, active surface that can easily assembled of biological soluble structure and targeting, imaging, and therapeutic molecules. 22 Unlike organic uorescent dyes, QDs are semiconductor particles which exhibit high photochemical stability, excellent resistance to chemical degradation, outstanding photodegradation and extremely large Stokes shi.…”
mentioning
confidence: 99%
“…To discriminate multi-MHs in CD-based sensors, other detection techniques like colorimetric changes, UV-VIS absorbance spectrophotometry also could be combined with fluorescence detection [112]. Naccache et al [113] reported the use of a dual absorbing/fluorescing CD system to detect four HM ions of Co(II), Fe(III), Hg(II), and Pb(II). In fluorescence assays, Co(II), Fe(III), Hg(II), and Pb(II) could be detected by ratiometric analysis based on the difference in the response of the blue and red fluorescence bands.…”
Section: Combination With Other Techniquesmentioning
confidence: 99%